Simpanan Karbon Pada Padang Lamun di Kawasan Pantai Mengiat, Nusa Dua Bali - I Kadek Vidyananda S Rahadiarta; I Dewa Nyoman Nurweda Putra; Yulianto Suteja (Fakultas Kelautan dan Perikanan Universitas Udayana, 2019)
Human activity is the most contributor of carbon dioxide gas (CO2) to the air. The oceans have an important role in the carbon cycle, about 93% of the Earth's CO2 is stored in the oceans. Seagrass is one of sea plants that has a role as carbon sinks in ocean. Seagrass beds are able to absorb carbon by an average 0.21 tons/ha and the important species are Enhalus acoroide. The aim of this study is determine the carbon storage in seagrass at aboveground (leaf), belowground (roots and rhizomes) and carbon storage on each species of seagrass obtained at Mengiat coastal area. Determination of sampling point refer to seagrass density that used by purposive sampling. This method was assumed to represent or describe the condition of this area. This research used dry dyeing method which components sample was destruction with 500oC inside the furnace. The results showed that carbon storage of seagrass at belowground (root and rhizoma) is 25.70 gC/m2, and aboveground (leaf) is 17.18 gC/m2. Carbon storage at belowground is higher than aboveground because carbon will accumulate in the sediment. The type of seagrass that is obtained at Mengiat coastal area is Thalassodendron ciliatum, Thalassia hemprichii, Cymodocea serrulata, Halodule uninervis, Cymodocea rotundata, and Syringodium isoetifolium, the highest carbon storage are 62.46 gC/m2 is owned by Thalassodendron ciliatum, and the lowest carbon storages are 17.25 gC/m2 is owned by Syringodium isoetifolium.